Host-mediated effects on fruit size variation of the hemiparasitic mistletoe Psittacanthus schiedeanus (Loranthaceae) - Ornelas , Juan Francisco; Vásquez-Aguilar, Antonio Acini (Instituto de Ecología, A.C., 2023)
Background and Aims: Most fruits of Psittacanthus mistletoes (Loranthaceae) depend on frugivorous birds for seed dispersal, and their spatial distribution patterns within and between hosts are strongly influenced by the behavior of seed dispersers. Despite the importance of birds in their dispersal and distribution, the effects of host species on fruit size variation have not been investigated to any large extent. The aim of this study was to characterize fruit size variation of Psittacanthus schiedeanus ripe fruits growing on different host species. We expect that the fruit size traits will vary according to the quality of host species, and that this variation will correspond to those in mistletoe reproductive success. Methods: Fully ripe fruits from Psittacanthus schiedeanus mistletoe plants growing on different host tree species were collected at two locations (Tlalnelhuayocan and Coapexpan) of cloud forest in central Veracruz, Mexico, measured (length and width and length of cupular pedicels) and weighed to describe fruit size differences. Key results: Cupular pedicel length and fruit size were significantly affected by host species. On average, longest cupular pedicels and larger fruits were found on plants growing on naturally growing Acacia pennatula, Quercus germana, Ostrya virginiana and Liquidambar styraciflua, whereas the smaller ones were found generally on cultivated host trees. Conclusions: The results provide us with valuable information for further species comparisons regarding the effects of host species on fruit size variation. Although the effects of host species on fruit size variation might vary across space, fruit size differences might be the result of host-resource differences. Further study on fruit selection and fruit handling by seed dispersers is needed to discuss whether the observed fruit size variation correlates with fruit selection and handling by main consumers, and with successful attachment and establishment to host branch after gut passage.